2022
DOI: 10.2196/33478
|View full text |Cite
|
Sign up to set email alerts
|

Use of Facial Morphology to Determine Nutritional Status in Older Adults: Opportunities and Challenges

Abstract: Undiagnosed malnutrition is a significant problem in high-income countries, which can reduce the quality of life of many individuals, particularly of older adults. Moreover, it can also inflate the costs of existing health care systems because of the many metabolic complications that it can cause. The current methods for assessing malnutrition can be cumbersome. A trained practitioner must be present to conduct an assessment, or patients must travel to facilities with specialized equipment to obtain their meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…These comprise the temporal fat pad, the preaponeurotic fat pad, the nasal fat pads, and the central fat pad. In cases of lipoatrophy, the loss of volume in these fat pads has been observed to accentuate the superior, medial, and lateral edges of the orbital rim, contributing to a sunken, skeletonized appearance 26 . Due to the limitations of camera‐captured images in providing depth information, we made the decision to use the orbital region and the rest of the face excluding the orbital region as two distinct features for inclusion in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These comprise the temporal fat pad, the preaponeurotic fat pad, the nasal fat pads, and the central fat pad. In cases of lipoatrophy, the loss of volume in these fat pads has been observed to accentuate the superior, medial, and lateral edges of the orbital rim, contributing to a sunken, skeletonized appearance 26 . Due to the limitations of camera‐captured images in providing depth information, we made the decision to use the orbital region and the rest of the face excluding the orbital region as two distinct features for inclusion in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of lipoatrophy, the loss of volume in these fat pads has been observed to accentuate the superior, medial, and lateral edges of the orbital rim, contributing to a sunken, skeletonized appearance. 26 Due to the limitations of camera‐captured images in providing depth information, we made the decision to use the orbital region and the rest of the face excluding the orbital region as two distinct features for inclusion in our study. Our analysis indicated that using the periorbital region as a feature yielded superior results with the same model.…”
Section: Discussionmentioning
confidence: 99%
“…12,26,27 The feasibility of diagnosing DRM using facial features has been validated. 28 For instance, certain bone processes and ridges, or the angulation of the jawline, may indicate there is a loss of fat or muscle tissue. [29][30][31] However, the use of facial features for malnutrition assessment has been limited by (1) the few categories and low prevalence of facial features, (2) tedious manual measurements, and (3) the lack of a golden standard measurement conducted by experienced physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Many nutrition assessments include a subjective evaluation of the head and face 12,26,27 . The feasibility of diagnosing DRM using facial features has been validated 28 . For instance, certain bone processes and ridges, or the angulation of the jawline, may indicate there is a loss of fat or muscle tissue 29–31 .…”
Section: Introductionmentioning
confidence: 99%
“…The face just like other parts of the body shows morphological variation from individual to individual. The shape of the face is determined by underlying bone, thickness and distribution of the underlying fat as well as the facial muscles [5].…”
Section: Introductionmentioning
confidence: 99%